The Bankruptcy Act in Hungary in the Interwar Period - Pétervári Máté (Law and History New Studies, 2021)
According to the Austro-Hungarian Compromise Hungary regained the independence and the Hungarian political elite desired to give a boost to development of the economy. The economic policy was determined by the liberal thinking in 19th century which based on the laissez-faire principle. The one of the suitable means to revive the economy of the Hungarian government was the forming of the appropriate legal regulation concerning to the commercial law. In 1875 the Hungarian National Assembly passed the first Hungarian Commercial Code, which supplemented by a new Bankruptcy Act in 1881. The new bankruptcy act in 1881 was a modern regulation, and it was appropriate to the requirements of the economic life. This Act remained in effect until the socialism after the Second World War, and it determined the Hungarian economy, therefore I examine the development of this act. The First World War changed the economy and the economic thinking, because it became possible that the executive power influence the economic life (evasion of price control, unfair competition, cartel law), therefore it is an interesting question, how the bankruptcy act functioned in Hungary in the Period of First World War. I present the practice of this act on the basis of archive material of the Royal Court of Appeal of Szeged.